Sociodemographic factors associated with anemia in children under 60 months - Román-Lazarte, Víctor (2022)
Objective: To determine the status of anemia and identify the sociodemographic factors associated with its development in children aged 6 to 59 months who attend first-level facilities, in the department of Tacna, during 2021. Material and methods: The study was carried out from a secondary database that collected data from children under 5 years of age who attended first-level health centers. A descriptive analysis and bivariate and multivariate analysis were performed, obtaining prevalence ratios and beta coefficients to determine the associated factors involved. Results: The prevalence of anemia in Tacna was 19.96 %. An inverse association was found between the variables age and health facility level (I-1, I-2, I-3 compared to level I-4), which were protective variables for the outcome. In the same way, the highest residence height in meters above sea level and the GDP per capita per district were directly associated with the presence of anemia. Conclusions: Despite the public policies and interventions carried out at the national level,there is still a great difference due to different sociodemographic characteristics. Poverty and height are directly related to rurality and social exclusion, which are independent factors for the development of anemia in the population under 5. More studies are required, mainly on intervention in the rural population and with low resources.